Enhancing Housing Development Guidelines for Sustainable Growth: A Proposal for Contextual Density Planning - Mufti, Norzaini; Mazlan, Ida Marlina (MAJ - Malaysia Architectural Journal, 2025)
Housing, considered a fundamental human right, underscores a nation's obligation to furnish adequate living accommodations for its citizens. This study focuses on Malaysia's housing industry, tracing its growth over the past millennium, with a significant surge since gaining independence in 1957. As Kuala Lumpur and its environs undergo substantial development, evolving regulatory frameworks aim to efficiently plan these expansions for the burgeoning local population. At the heart of this discourse is the concept of density, signifying the allowable number of accommodation units within a specified area. While current metrics like units per acre (u.p.a) and persons per acre (p.p.a) effectively guide development guidelines, they often fall short in considering existing facilities in the vicinity and responsiveness to immediate surroundings. This paper proposes a paradigm shift by advocating for development guidelines that encompass facilities within a 500-meter radius of the proposed site using the exploratory research design method to acquire an understanding of a complex issue in its real-life context. Building on decades of housing industry development, the paper identifies opportunities to enhance and optimize housing facility quality and user satisfaction. The proposed contextual density planning seeks to minimize redundancy and enhance efficiency by incorporating facilities within a 500-meter radius into development guidelines. Contributing to the discourse on sustainable urban development, this paper advocates for a more nuanced approach aligning housing projects with existing socio-cultural and physical contexts. By considering the broader environment, the proposed conceptual guidelines aim to foster more efficient, sustainable, and contextually relevant housing developments, thereby positively impacting both the industry and its stakeholders.